Estimates of the Returns to Schooling from Sibling Data: Fathers, Sons, and Brothers - Ashenfelter, Orley; Zimmerman, David J. (The Review of Economics and Statistics, 1997)
Data on brothers and on fathers and sons from the National Longitudinal Survey are used to consider the impact of omitted variables and measurement errors on the economic returns to schooling. The analysis suggests that the upward bias in estimated returns due to omitted variables is likely offset by an equal downward bias resulting from measurement errors in reported schooling. Controlling for both of these potential sources of bias yields results comparable to conventional regression estimates of the economic return to schooling.